(Z)-3-Anilino-1,3-diphenylprop-2-en-1-one - Li-Ping Zhang; Lin-Juan Wei; Ming-Qing Chen; Zhan-Hui Zhang (Acta Crystallographica Section E, 2008)
In the title compound, C21H17NO, the phenyl ring directly linked to the carbonyl group is oriented at an angle of 7.3 (2)° with respect to the aniline ring, and at an angle of 55.6 (2)° with respect to the other phenyl ring. There is an intramolecular hydrogen bond involving the NH group and the carbonyl O atom. The crystal structure is stabilized by weak C—H...π interactions, which link the molecules into a herringbone arrangement.